ORGANOLEPTIC AND DIETARY FIBER QUALITY OF BLACK PIGEON PEA FLOUR AS BIOENCAPSULATION MATERIAL - Lina Oktavia Rahayu; Ambar Fidyasari (Sekolah Tinggi Pariwisata Mataram, 2022)
Gude beans are one type of legume that has a fairly high nutritional value. The existence of gude beans is currently only used as a side dish, mixed as a staple food and even for animal feed. To increase its economic value, gude beans are used as bioencapsulation material. One of the requirements for bioencapsulation technology is that it can be sensory and economical. The purpose of this study was to determine the organoleptic results of the process of making gude bean flour and the content of dietary fiber. This research is included in experimental research with descriptive data analysis used. The results obtained from organoleptic quality testing include color 2.25 good category, taste 2.45 good category, texture 2.80 good category and aroma 3.00 good category. Color reader test results sifted gude flour with a brightness degree of 49.0, redness 18.3, yelloness 27.1, while unsifted gude flour has a brightness degree of 46.90, redness 24.7, yelloness 30.6. the results obtained 23.28 grams/100 grams. In conclusion, the results of gude bean flour in physical quality in terms of color, taste and texture and aroma were acceptable to the panelists, while the results of dietary fiber were categorized as quite high in fiber.